Root Canal Morphology of Mandibular First Permanent Molars in an Indian Population - Hemant Ramesh Chourasia; Ganesh K. Meshram; Manjusha Warhadpande; Darshan Dakshindas (International Journal of Dentistry, 2012)
An in vitro study was performed to determine the number of roots, root canals per tooth, root canal configurations, and frequency of isthmi and apical deltas in mandibular first permanent molars in an Indian population. Hundred and fifty mandibular first permanent molars were collected and subjected to clearing technique. The cleared teeth were examined in a stereomicroscope under 7.5x magnifications. The canal configurations were categorized using Vertucci's classification. Overall 94.6% of the mandibular first molars had two roots, and 5.3% had extradistal roots (distolingual root). In addition, 64% of the specimens had three root canals, and 36% had four root canals. The most common canal configurations of mesial and distal roots were Vertucci type IV (54%) and type I (65.3%), respectively. Clinician should be aware of the complex root canal morphology of mandibular first molars among the Indian population before and during the root canal treatment.